2020
DOI: 10.1007/s40801-020-00207-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Observational Study of ALK-Inhibitor Therapy Sequencing and Outcomes in Patients with ALK-Positive Non-small Cell Lung Cancer

Abstract: Background Data are sparse concerning the sequential use of multiple anaplastic lymphoma kinase (ALK) inhibitors for ALK-positive locally advanced or metastatic non-small cell lung cancer (NSCLC). Objective This study investigated sequencing and outcomes among patients receiving multiple ALK inhibitors. Patients and Methods This was a retrospective observational cohort study of adult patients with ALK-positive NSCLC treated with available fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Sequential administration of effective drugs is critical in order to maximize therapeutic benefit and the survival of patients with NSCLC, main focus of previous studies has been the efficacy rather than the feasibility of therapeutic sequencing (8,(16)(17)(18)(19). Systematic analysis of the latter is endowed with serious difficulties, mainly the rarity and generally better prognosis of + NSCLC, the analysis regarding chemotherapy was performed in the subset of deceased patients (n=74, Figure 1), for which the entire disease trajectory could be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential administration of effective drugs is critical in order to maximize therapeutic benefit and the survival of patients with NSCLC, main focus of previous studies has been the efficacy rather than the feasibility of therapeutic sequencing (8,(16)(17)(18)(19). Systematic analysis of the latter is endowed with serious difficulties, mainly the rarity and generally better prognosis of + NSCLC, the analysis regarding chemotherapy was performed in the subset of deceased patients (n=74, Figure 1), for which the entire disease trajectory could be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of titles and abstracts allowed the selection of 131 potentially eligible studies. Among them, a total of 32 studies fulfilled the eligibility criteria and were finally included into the review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. No further studies were retrieved through a snowballing search.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six out of 32 included studies used rcEHD from North America [ 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], two studies used data from Asia [ 24 , 32 ], three from Europe [ 26 , 42 , 55 ], and one from Australia [ 25 ]. Thirteen studies used record linkage of ≥1 type of data source [ 24 , 25 , 26 , 28 , 30 , 32 , 35 , 36 , 42 , 44 , 45 , 50 , 55 ], while 19 studies were based on one data source type only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ndings indicated that circRNAs are closely related to the occurrence and development of diseases and maybe a potential target for the future diagnosis and treatment of the disease. However, most of the studies on circular RNA and non-small cell lung describe only a few genes description, and the mechanism of systematic molecular regulation is yet to be elucidated [21][22].…”
Section: Introductionmentioning
confidence: 99%